The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.memsci.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Structure/property relationship of Nafion XL composite membranes

Abstract: Perfluorosulfonic-acid (PFSA) ionomer membranes (most commonly Nafion ® ) are currently the prototypical proton-exchange-membrane in polymer-electrolyte fuel cells (PEFCs), for which durability still represents a technical barrier to their commercialization. In an effort to address the durability demands, PFSA membranes with reinforcement and/or stabilizers have become of great interest as they have demonstrated superior durability in PEFCs compared to their unreinforced analogues. One such particular membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
140
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(148 citation statements)
references
References 59 publications
8
140
0
Order By: Relevance
“…Empirical relationships between Ce ion transport properties and PEM water content.-Using water sorption data for Nafion XL PEMs, 19 empirical relationships between Ce ion diffusivity and mobility as a function of PEM water content (defined as λ = nH 2 O/nSO 3 H) may be estimated. Assuming that ion diffusivity and mobility are zero for λ = 0, linear fitting of the data yields:…”
Section: Discussionmentioning
confidence: 99%
“…Empirical relationships between Ce ion transport properties and PEM water content.-Using water sorption data for Nafion XL PEMs, 19 empirical relationships between Ce ion diffusivity and mobility as a function of PEM water content (defined as λ = nH 2 O/nSO 3 H) may be estimated. Assuming that ion diffusivity and mobility are zero for λ = 0, linear fitting of the data yields:…”
Section: Discussionmentioning
confidence: 99%
“…The nominal thicknesses are ∼12 μm for the PTFE layer and ∼9 μm for each external PFSA layer. 10,17 A reinforced membrane which operated in Axane Evopac fuel cell system was also investigated. This system, composed of two stacks of 55 cells, was studied in References 18 and 12.…”
Section: Methodsmentioning
confidence: 99%
“…This was due to possible structural changes, leading to internal stress relaxation in the expanded PTFE membranes. The cross‐sections of Nafion™ XL membrane prior to and after pretreatment are shown in Figures 7d to 7g . Prior to pretreatment, the fibers are dispersed along the thickness direction, as shown in Figures d and e.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the improvement in mechanical stability is not at the expense of reduced performance. It was found that Nafion™ XL membrane showed comparable conductivity with the benchmark material Nafion™ 212 membrane . In addition, The Nafion™ XL composite membrane exhibited longer lifetime during accelerated stress test (AST) and field test , .…”
Section: Introductionmentioning
confidence: 99%